Inhalation performance analysis of dry powder inhaler - Azhar, Muhammad Ikhmal; Akram, Muhammad Waseem; Naharudin, Idanawati (Faculty of Pharmacy, 2025)
Dry powder inhalers (DPIs) are commonly used to treat respiratory diseases, particularly asthma, lung cancer, and chronic obstructive pulmonary disease, by delivering medications directly to the lungs. This review explores the influence of key formulation parameters such as particle size, morphology, surface roughness, and excipients on the inhalation performance and efficiency of DPIs. A comprehensive analysis of recent studies was performed to understand how these variables affect aerosolization and inhalation performance. The findings highlight that particle size is directly correlated with fine particle fraction (FPF), smaller particles (<5 µm) exhibit higher FPF (~80 %), and are suitable for targeting lower airways. Regarding morphology, elongated or needle-shaped particles experience an increased aerodynamic drag, aiding their deposition in the lower regions of the respiratory tract. In contrast, particles with smooth surfaces exhibit less interparticle adhesion and cohesion forces, leading to improved dispersion and aerosolization. Moreover, the incorporation of lubricant is shown to occupy the binding sites of the carrier, reduce agglomeration, and promote aerosolization and delivery efficiency of DPIs. In conclusion, DPIs offer strong potential to achieve targeted delivery to designated regions of the upper and lower respiratory tract through particle size modulation and formulation approaches.